MENINGKATKANKKEMAMPUAN KOMUNIAKSI MATEMATISMMELALUI MODELPPEMBELAJARANKKOOPERATIF TIPE THINK TALK WRITE - Aulia Rasdiana (Departemen Matematika, 2020)
Oneoofttheggoalsoofmmathematicsllearning ismmathematicalccommunication. But in reality inSSMP Negeri 1 Padangtthisaability issstill notooptimal. Seenffrom therresultsoof the initial tests showed the low mathematicalccommunication skills. Oneeeffort tooovercome thispproblem isbby applying a cooperativeLlearningMmodelTThink TalkWWrite type to improve students' Icommunication skills. Theppurpose of thissstudy is toffind outaandddescribe that the ThinktTalk Write cooperative learningmmodelhhas a tendency to improve mathematicalncommunication skills. Thisstype ofrresearch issthesstudyoof literature onpimproving mathematicalccommunicationsskills through theccooperativeelearningmmodeltThinktTalkwWriteetype. The conclusion offthis literature study is the cooperativellearningmmodeltThinktTalkwWrite type tends tooimprovemmathematical communicationsskills seen from students to be helped inmimproving mathematicalccommunication skillssfrom thesstages carried out in theccooperativeelearningmmodeltThinktTalkwWriteetype that is presented in related articles and corresponds to indicatorsoofccommunication communicationsskills mathematicali.Keywords — Think Talk Write, Mathematical Comunicati